Physician advice for smoking cessation (Review) (2013)
Background Healthcare professionals frequently advise people to improve their health by stopping smoking. Such advice may be brief, or part of more intensive interventions. Objectives The aims of this review were to assess the effectiveness of advice from physicians in promoting smoking cessation; to compare minimal interventions by physicians with more intensive interventions; to assess the effectiveness of various aids to advice in promoting smoking cessation, and to determine the effect of anti‐smoking advice on disease‐specific and all‐cause mortality. Search methods We searched the Cochrane Tobacco Addiction Group trials register in January 2013 for trials of interventions involving physicians. We also searched Latin American databases through BVS (Virtual Library in Health) in February 2013.